Chyme Reinfusion in Intestinal Failure Related to Temporary Double Enterostomies and Enteroatmospheric Fistulas - Picot, Denis (Nutrients, 2020)
Some temporary double enterostomies (DES) or entero-atmospheric fistulas (EAF) have high output and are responsible for Type 2 intestinal failure. Intravenous supplementations (IVS) for parenteral nutrition and hydration compensate for intestinal losses. Chyme reinfusion (CR) artificially restores continuity pending surgical closure. CR treats intestinal failure and is recommended by European Society for Clinical Nutrition and Metabolism (ESPEN) and American Society for Parenteral and Enteral Nutrition (ASPEN) when possible. The objective of this study was to show changes in nutritional status, intestinal function, liver tests, IVS needs during CR, and the feasibility of continuing it at home. A retrospective study of 306 admitted patients treated with CR from 2000 to 2018 was conducted. CR was permanent such that a peristaltic pump sucked the upstream chyme and reinfused it immediately in a tube inserted into the downstream intestine. Weight, plasma albumin, daily volumes of intestinal and fecal losses, intestinal nitrogen, and lipid absorption coefficients, plasma citrulline, liver tests, and calculated indices were compared before and during CR in patients who had both measurements. The patients included 185 males and 121 females and were 63 ± 15 years old. There were 37 (12%), 269 (88%) patients with EAF and DES, respectively. The proximal small bowel length from the duodeno-jejunal angle was 108 ± 67 cm (n = 232), and the length of distal small intestine was 117 ± 72 cm (n = 253). The median CR start was 5 d (quartile 25–75%, 2–10) after admission and continued for 64 d (45–95), including 81 patients at home for 47 d (28–74). Oral feeding was exclusive 171(56%), with enteral supplement 122 (42%), or with IVS 23 (7%). Before CR, 211 (69%) patients had IVS for nutrition (77%) or for hydration (23%). IVS were stopped in 188 (89%) 2 d (0–7) after the beginning of CR and continued in 23 (11%) with lower volumes. Nutritional status improved with respect to weight gain (+3.5 ± 8.4%) and albumin (+5.4 ± 5.8 g/L). Intestinal failure was cured in the majority of cases as evidenced by the decrease in intestinal losses by 2096 ± 959 mL/d, the increase in absorption of nitrogen 32 ± 20%, of lipids 43 ± 30%, and the improvement of citrulline 13.1 ± 8.1 µmol/L. The citrulline increase was correlated with the length of the distal intestine. The number of patients with at least one liver test >2N decreased from 84–40%. In cases of Type 2 intestinal failure related to DES or FAE with an accessible and functional distal small bowel segment, CR restored intestinal functions, reduced the need of IVS by 89% and helped improve nutritional status and liver tests. There were no vital complications or infectious diarrhea described to date. CR can become the first-line treatment for intestinal failure related to double enterostomy and high output fistulas.